Development of bullous pemphigoid during treatment of psoriasis with ustekinumab: a case report and literature review - Kong, Luyang; Huang, Dawei; Lu, Jiajing; Zhang, Yuexin; Li, Ying; Yi, Xuemei; Shi, Yuling (Frontiers in Medicine, 2023)
Ustekinumab is a biological therapy that has been approved for treating moderate-to-severe psoriasis. Although injection site reactions, nasopharyngitis, headaches, and infections are the common adverse events associated with ustekinumab, the development of bullous pemphigoid (BP) is also thought to be related to ustekinumab. Given that psoriasis itself can be complicated by BP, it is worthwhile to investigate the relationship between ustekinumab, psoriasis, and BP. Here we report a case of a male patient who developed BP twice after psoriasis treatment with ustekinumab. The patient's psoriasis and BP were brought under control by discontinuing ustekinumab and administering methotrexate, minocycline, and topical corticosteroids. Because of the increasing use of biologics in patients with psoriasis, BP should be considered a potential adverse event associated with ustekinumab.